ESTETIKA DAKWAH DALAM LAGU JAWA - Ibad, Tamyizul (Millah: Journal of Religious Studies, 2010)
The study elaborates the arts of dakwah in the Javanese songs; Sluku-sluku Bathok and Turi-turi Putih. Both songs are one of the dakwah strategies conducted by the previous Ulemas in order that the society could accept the dakwah effectively. The use of the Javanese songs in the dakwah has become a particular characteristic of acculturation of Islam and Javanese culture. In fact, Javanese society has pleasantly accepted the Islamic dakwah.